On Higher-Order Sequential Fractional Differential Inclusions with Nonlocal Three-Point Boundary Conditions - Bashir Ahmad; Sotiris K. Ntouyas (Abstract and Applied Analysis)
We study a nonlinear three-point boundary value problem of sequential fractional differential inclusions of order ξ+1 with n-1<ξ≤n, n≥2. Some new existence results for convex as well as nonconvex multivalued maps are obtained by using standard fixed point theorems. The paper concludes with an example.